Kontradiksi Perilaku Republik Rakyat China di Asia Tenggara: Geopolitik dan Kepentingan Nasional - Arif Nugraha; Obsatar Sinaga; Windy Dermawan (Jurnal Studi Ilmu Sosial dan Politik, 2022)
Purpose: This study will explain the People's Republic of China's (PRC) national interest through international relations activities in the Southeast Asian region. Activities that occur between PRC and states in Southeast Asia are cooperation and conflict at the same time. One form of cooperation that occurs between the PRC and countries in Southeast Asia is the Belt and Road Initiatives (BRI) mega project. Meanwhile, a territorial dispute in the South China Sea is one form of conflict that arises between the PRC and states in Southeast Asia. Methodology: The research method used in this research is a qualitative research method with a descriptive approach. This study will use the concepts of geopolitics and national interests as a research knife to explain the importance of the Southeast Asian region to the PRC, China's behavior in the Southeast Asia region, and PRC intentions. Results: Southeast Asia is of great importance to PRC national interests. The strategic location, natural resources, and countries in the region have the potential to fulfill PRC national interests. PRC has both cooperative and conflict relations with countries in Southeast Asia. Bilateral and multilateral cooperation between PRC and Southeast Asian countries has positively impacted both sides. One form of collaboration between the PRC and Southeast Asian countries is the BRI, and one conflict is the dispute in the South China Sea. Good relations are not a guarantee of avoiding a conflict and vice versa. Ultimately, the state will make a rational choice that will produce a decision or policy that can accommodate its national interests.